Methodological assessment of the reduction of the content of impurities in nimodipine emulsion via the use of 21 amino acid protection - Xie YQ (Dove Medical Press, 2017)
Yiqiao Xie,1,* Zhiquan Zhuang,2,* Shu Zhang,1 Zihua Xia,1 De Chen,1 Kaiyan Fan,1 Jialin Ren,1 CuiCui Lin,1 Yanzhong Chen,1 Fan Yang1 1Department of Pharmaceutics, Guangdong Pharmaceutical University, 2Department of Pharmacy, First Affiliated Hospital of Guangdong Pharmaceutical University, Guangzhou, Guangdong, People’s Republic of China *These authors contributed equally to this work Purpose: The present study examined the factors affecting the content of impurities of nimodipine (NMP) emulsion and the associated methods of compound protection.Methods: Destructive testing of NMP emulsion and its active pharmaceutical ingredient (API) were conducted, and ultracentrifugation was used to study the content of impurities in two phases. The impurity of NMP was measured under different potential of hydrogen (pH) conditions, antioxidants and pH-adjusting agents.Results: Following destruction, the degradation of NMP notably occurred in the basic environment. The consumption of the pH-adjusting agent NaOH was proportional to the production of impurities since the inorganic base and/or acid promoted the degradation of NMP. The organic antioxidants, notably amino acids with an appropriate length of intermediate chain and electron-donating side group, exhibited improved antioxidant effects compared with inorganic antioxidants. The minimal amount of impurities was produced following addition of 0.04% lysine and 0.06% leucine in the aqueous phase and adjustment of the pH to a range of 7.5–8.0 in the presence of acetic acid solution.Conclusion: NMP was more prone to degradation in an oxidative environment, in an aqueous phase and/or in the presence of inorganic pH-adjusting agents and antioxidants. The appropriate antioxidant and pH-adjusting agent should be selected according to the chemical structure, while destructive testing of the drug is considered to play the optimal protective effect. Keywords: nimodipine emulsion, impurity, destructive testing, ultracentrifugation, antioxidation, pH